TANGGUNG GUGAT PENGELOLA HOTEL TERHADAP HILANGNYA BARANG PRIBADI TAMU HOTEL - Ruslan, Herlina; Borman, M. Syahrul; Handayati, Nur; Sidarta, Dudik Djaja (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2025)
The standard clause which states "Loss of personal items is not the responsibility of the hotel" results in weak consumer legal protection for the use of accommodation or hotel services. The aim of the research is to analyze the hotel's responsibility in providing security guarantees for hotel’s guests. The type of research is normative juridical legal research. The research approach used is the Statue Approach and Case Approach. The method of collecting legal materials is through literature study with normative legal material analysis techniques. The results of the research prove that the responsibility of hotels as lodging service providers in providing security guarantees for hotel’s guests is that they are obliged to provide consumer comfort and security in the hotel area they manage and in the event of a loss provide compensation for hotel’s guests losses. The consumer protection provided to hotel’s guests in cases of loss of goods inside hotel room is the existence of consumer rights including the right to security and safety, the right to information, the right to be heard and the right to compensation.